WAAC-2 Cause of the Death Sea turtle Stranded in Nesting Beach (Paloh, West Kalimantan) Period from February to April 2018 - Maulid Dio; Dwi Suprapti; Fidry R Ikhwan; IA Kusuma Dewi (Hemera Zoa, 2018)
Coastal Paloh an important habitat for four species of sea turtles are the Green (Chelonia mydas), Hawksbill (Eretmochelys imbricate), Olive ridley (Lepidochelys olivacea) and Leatherback (Dermochelys coriacea). Aside from being a nesting habitat, the area is also a habitat for feeding, and mating habitat and migration path or traffic seaturtle (Suprapti, 2012). Not only for sea turtles traffic has also become important for a variety of vessels between both countries fishing vessels, tankers up cargo. Given the geographic location is directly opposite the South China Sea that is surrounded by several countries.But unfortunately, the South China Sea is strategically important as well as give a bad condition for Paloh seas. Because the area is the location of the trash stream (marine debris) from various countries who tipped rubbish on the beach strandings Paloh. As for the garbage found a variety of forms, both organic waste and non-organic, but Mostly in the form of waste plastic and bottles of mineral water.Not only trash that washed up on shore Paloh. In the last 2 months at least found 21 seaturtles (Table 1) were also stranded together piles of garbage and solid black colored chemical material at the seaside 7 which drifted onto the beach Paloh. This incident is considered remarkable so it is important for researchers, especially veterinarian determine the cause of death in the mass stranded turtle nesting beaches Paloh.